2007
DOI: 10.1002/ijc.22405
|View full text |Cite
|
Sign up to set email alerts
|

The use of histone deacetylase inhibitor FK228 and DNA hypomethylation agent 5‐azacytidine in human bladder cancer therapy

Abstract: The long-term disease-free survival in patients with metastatic transitional cell carcinoma (TCC) is still considerably low. Novel chemotherapeutic agents are needed to decrease the morbidity and mortality of TCC. In this study, we have evaluated several epigenetic modifiers for their therapeutic application in bladder cancer. Both histone deacetylase inhibitors (FK228, TSA) and DNA hypomethylating agent (5-Azacytidine) were tested using in vitro assays such as cell viability, cell cycle analysis and western b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
36
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 45 publications
(67 reference statements)
7
36
1
Order By: Relevance
“…Similar results have been shown for ectopic expression of p21 or induction of p21 by different mechanisms [22][23][24][25][26][27] . Concomitantly, results of flow cytometry showed that dsP21 transfection caused a G1 arrest, with a significant decrease in S-phase.…”
Section: Discussionsupporting
confidence: 86%
“…Similar results have been shown for ectopic expression of p21 or induction of p21 by different mechanisms [22][23][24][25][26][27] . Concomitantly, results of flow cytometry showed that dsP21 transfection caused a G1 arrest, with a significant decrease in S-phase.…”
Section: Discussionsupporting
confidence: 86%
“…6B). The induction of p21 seems to be a hallmark of histone deacetylation (32), and p21 expression is associated with the antiproliferative effect of HDACI (11,33). Based on data from this study, we believe that p21 induction is critical for the growth inhibition and apoptosis of TCC.…”
Section: Discussionmentioning
confidence: 69%
“…Thus, targeting epigenetic machinery with different inhibitors (9,10) has become a new avenue of cancer therapy. Recently, we have shown a potent in vitro growth inhibitory effect of DNA hypomethylating agent (e.g., 5-azacytidine) and romidepsin on several human TCC cell lines (11). Using xenograft models, we concluded that romidepsin is a promising agent for human bladder cancer (11).…”
mentioning
confidence: 90%
“…It inhibits HDAC1 and HDAC2 with IC50 of 1.6 and 3.9 nM by noncell base and cell-based assays, respectively [18][19][20][21]. In MM, romidepsine induces apoptosis both in cell lines and primary tumor cells from patients, associated with downregulation of Bcl-2, BCL-xL and Mcl-1 expression [22].…”
Section: Romidepsine (Fr901228 Fk228)mentioning
confidence: 99%